Greetings from the South from the Cabinet 227: My heart is still alive, “so, come on over and praise the artists”! - Trifunović, Vesna S. (Sociološki pregled, 2019)
Book Review: Dragoljub B. Đorđević, I asked a little snail: my sociological story about Šaban Bajramović. Beograd, Službeni glasnik, 2018, 334 pp.